(untitled) (Latakia University Journal -Engineering Sciences Series, 2019)
يتناول هذا البحث دراسة غازات العادم الصادرة عن المحركات البحرية, والتي تعدّ من أهم مسائل الأمن البيئي لمحركات الديزل البحرية المستخدمة في دفع السفن. تم في هذا البحث تصميم منظومة فرعية لتحديد غازات العادم لمحركات الديزل البحرية، وهي منظومة تعتمد في تحديد مكونات الخليط الغازي على فرضية التكافؤ الخطي المعتمد في المخططات الحرارية،كما تم إدراج المخطط البنيوي والمبدأ للمنظومة الفرعية وخوارزمية عملها, واستخدمت جملة معادلات ذات درجات متناقصة لحل المسائل الرياضية المستخدمة في جمع المعطيات ومعالجتها. This research is aimed at studying exhaust gases of marine engines, which are considered one of the most important problems of ecological security for marine engines used for ship propulsion. In this study, a sub-system is designed to determine exhaust gases of diesel marine engines. To determine components of gas mixture, the sub-system depends on supposition linear additivity of thermograms. A schematic representation of the structure and principle of sub-system, and the algorithm of its work, are explained in this paper. Also, a set of depressed dimension equations is used to solve mathematical problems used for collecting and analyzing data.